The impact of antiviral therapy for HCV on kidney disease: a systematic review and meta-analysis - Fabrizio Fabrizi (Nefrología, 2020)
Background: Controversy persists about the role of hepatitis C as a risk factor for developing kidney disease in the general population. Some authors have evaluated the effect of antiviral therapy for HCV on the risk of kidney disease. Study Aims and Design: A systematic review of the published medical literature was performed to assess whether antiviral therapy for HCV has an independent impact on kidney survival in the adult general population. A random effects model was used to generate an overall estimate of the risk of kidney disease after anti-HCV therapy across the published studies. Meta-regression and stratified analysis were also carried out. Results: Fifteen studies were eligible (n = 356, 285 patients) and separate meta-analyses were conducted according to the outcome. Pooling studies based on viral responses (n = 7; 34,763 individual patients) demonstrated a relationship between sustained viral response and lower frequency of kidney disease; the overall estimate for adjusted risk of kidney disease was 2.50 (95% CI, 1.41; 4.41) (p = 0.0016) and between-study heterogeneity was found (p-value by Q test = 0.004). Aggregation of studies comparing treated vs untreated cohorts (n = 8, n = 333,312 patients) revealed an association between anti-HCV therapy and lower risk of kidney disease. The overall estimate for adjusted risk of kidney disease across the eight studies was 0.39 (95% CI, 0.25; 0.612) (p = 0.0001). Meta-regression showed that the effectiveness of antiviral therapy in reducing the frequency of kidney disease diminishes as cirrhosis (p = 0.02) and HBV infection (p = 0.0001) increase among HCV-infected individuals. Conclusions: Antiviral therapy for HCV lowers the risk of kidney disease among HCV-infected individuals. Studies to understand the mechanisms underlying this association are ongoing. Resumen: Antecedentes: Sigue existiendo controversia acerca del rol de la hepatitis C como factor de riesgo de desarrollo de enfermedades renales en la población general. Algunos autores han evaluado el efecto de la terapia antiviral para el VHC en el riesgo de enfermedad renal. Objetivos y diseño del estudio: Se realizó una revisión sistemática de la literatura médica publicada, para evaluar si la terapia antiviral para el VHC tenía un impacto independiente en la supervivencia renal en la población adulta general. Se utilizó un modelo de efectos aleatorios para generar una estimación general del riesgo de enfermedad renal tras la terapia anti-VHC, entre los estudios publicados. También se realizaron análisis de meta-regresión y estratificados. Resultados: Quince estudios resultaron elegibles (n = 356, 285 pacientes), realizándose meta-análisis separados con arreglo al resultado. Los estudios agrupados basados en las respuestas virales (n = 7; 34.763 pacientes individuales) demostraron una relación entre la respuesta viral sostenida y la menor frecuencia de enfermedad renal; la estimación general para el riesgo ajustado de enfermedad renal fue de 2,5 (95% IC, 1,41; 4,41) (p = 0,0016), encontrándose una heterogeneidad entre estudios (valor p con prueba Q = 0,004). La suma de estudios comparativos de cohortes tratadas vs no tratadas (n = 8, n = 333.312 pacientes) reveló una asociación entre la terapia anti-VHC y el menor riesgo de enfermedad renal. La estimación general para el riesgo ajustado de enfermedad renal entre ocho estudios fue de 0,39 (95% IC, 0,25; 0,612) (p = 0,0001). La meta-regresión reflejó que la efectividad de la terapia antiviral para reducir la frecuencia de enfermedad renal disminuye a medida que aumentan los casos de cirrosis (p = 0,02) e infección por VHB (p = 0,0001) entre los individuos infectados de VHC. Conclusiones: La terapia antiviral para el VHC disminuye el riesgo de enfermedad renal entre los individuos infectados de VHC. Son continuos los estudios para comprender los mecanismos subyacentes a esta asociación.